EU referenda in the Baltics: understanding the results at the regional level - Mihails Hazans (European Regional Science Association (ERSA), 2004)
The papers analyses regional differences in EU referenda results in Estonia, Latvia, and Lithuania. In each of the three countries, other things being equal, high income regions were significantly more pro-European than low-income ones, while regions with a high share of ethnic minorities were significantly more opposed to the enlargement than other regions. The ethnic effect was strongest in Latvia and weakest in Estonia. These findings clearly indicate necessity of stronger efforts both in integration of the Baltic societies and in the promotion of reliable EU information, especially in less developed regions. On the other hand, we confirm the findings from earlier referenda that support from EU membersip does not come primarily from regions and groups that are likely to benefit from EU-wide redistribution. In Latvia and Estonia the regions bordering with Russia or Belarus were substantially less in favour of EU membership than other regions (controlling for ethnic composition and economic factors). In Latvia, regions on the borders with EU accession countries were significantly more pro-European than other regions. Keywords: European Union, European integration, cross-border development, ethnic minorities, regional income differentials. JEL Categories: D72, J15, P52, R1
Keywords: D72; J15; P52; R1; 330; European Union; European integration; cross-border development; ethnic minorities; regional income differentials